Neurochemical correlates of caudate atrophy in Huntington's disease. Issue 3 (17th January 2014) - Padowski, Jeannie M.; Weaver, Kurt E.; Richards, Todd L.; Laurino, Mercy Y.; Samii, Ali; Aylward, Elizabeth H.; Conley, Kevin E.
ABSTRACT: The precise pathogenic mechanisms of Huntington's disease (HD) are unknown but can be tested in vivo using proton magnetic resonance spectroscopy ( 1 H MRS) to measure neurochemical changes. The objective of this study was to evaluate neurochemical differences in HD gene mutation carriers (HGMCs) versus controls and to investigate relationships among function, brain structure, and neurochemistry in HD. Because previous 1 H MRS studies have yielded varied conclusions about HD neurochemical changes, an additional goal was to compare two 1 H MRS data analysis approaches. HGMCs with premanifest to early HD and controls underwent evaluation of motor function, magnetic resonance imaging, and localized 1 H MRS in the caudate and the frontal lobe. Analytical approaches that were tested included absolute quantitation (unsuppressed water signal as an internal reference) and relative quantification (calculating ratios of all neurochemical signals within a voxel). We identified a suite of neurochemicals that were reduced in concentration proportionally to loss of caudate volume in HGMCs. Caudate concentrations of N‐acetylaspartate (NAA), creatine, choline, and caudate and frontal lobe concentrations of glutamate plus glutamine (Glx) and glutamate were correlated with caudate volume in HGMCs. The relative, but not the absolute, quantitation approach revealed disease‐related differences; the Glx signal was decreased relative to other neurochemicals in the caudate of HGMCs versus controls. This is the first study to demonstrate a correlation among structure, function, and chemical measures in HD brain. Additionally, we demonstrate that a relative quantitation approach may enable the magnification of subtle differences between groups. Observation of decreased Glx suggests that glutamate signaling may be disrupted relatively early in HD, which has important implications for therapeutic approaches. © 2014 International Parkinson and Movement Disorder Society